INDONESIAN HEALTH IN CRISIS: ASSOCIATION BETWEEN COGNITIVE FUNCTION AND DEPRESSION: Krisis Kesehatan di Indonesia: Hubungan antara Fungsi Kognitif dan Depresi berdasarkan Indonesian Family Life Survey - Rikky Arya Pangestu; Iswana Zahraa Hidayati; Santi Martini; Firman Suryadi Rahman; Nayla Mohamed Gomaa Nasr; Muhammad Aziz Rahman (Jurnal Berkala Epidemiologi, 2023)
Background: Depression differs from common mood swings and short-lived emotions. It has been extensively reported that cognitive impairment is associated with depression. Depression affects all aspects of life and interferes with productivity. Purpose: This study examined the association between cognitive function and depression in an Indonesian working age group. Methods: We used data from longitudinal socioeconomic and health surveys based on the fifth wave of the Indonesian Family Life Survey (IFLS) from October 2014 to April 2015. Household members aged 15-64 were included in the analysis. Depression was assessed using the Short Center for Epidemiological Research Depression Scale (CESD). Cognitive function was measured using the Cognitive Status Telephone Interview (TICS). Simple linear regression analysis was performed to examine the association between cognitive function and depression. Results: A total of 10,628 households were included. Most respondents had good cognitive function (61.84%) and no depression (82.19%). A simple linear regression analysis showed that household members with good cognitive functioning had a significantly lower risk of developing depression compared to household members with cognitive decline, he was significantly 1.28 lower. Conclusion: This study found a significant association between cognitive function and depression in the productive-age group. Further research exploring variables related to depression other than cognitive function is recommended. Health care providers should provide education, counselling, and training sessions related to healthy lifestyles and positive mindsets to prevent depression.